Masculinization of Nile tilapia (Oreochromis niloticus) by administration of bull testes meal - Muslim, Muslim; Junior, M. Zairin; Utomo, Nur Bambang Priyo (Jurnal Akuakultur Indonesia, 2011)
The synthetic steroid 17α-Methyltestosteron (MT) is commonly used as a feed additive to produce male population of Nile tilapia (Oreochromis niloticus). The use of synthetic testosterone hormone is not recommended in Indonesia. This study was conducted to evaluate the effect of natural testosterone hormone in bull testes meal (BTM) on the masculinization of Nile tilapia using validated aceto carmine squash method of gonads of the fish. Experimental design was utilized two factors experiments in completely randomized design. Fry kept in 40-L glass aquaria at a density of 40 fry/aquarium. Fry (7 dph) received the BTM  for 7 days (T1), 14 days (T2) and 21 days (T3) and doses 0% (D1), 3% (D2), 6% (D3), and 9% (D4).  When treatment was these results, indicated that significant (P≥0.05) masculinization occurred only in the group treated of BTM and no treated of BTM. In the group treated of BTM, doses and duration treatment is not significant. The percentage of male fish 83.3% (9%-7d, 9%-21d, 6%-21d: doses and duration, respectively), higher than all group. Survival rate of fry (95-99.5%) is not affected by treatment BTM (no significant P≥0.05). Fish growth was significantly affected by treatment BTM compare with no treated of BTM. The highest growth performance of fry were obtained with the 9% BTM.Key words: masculinization, nile tilapia, bull testes meal ABSTRAKSteroid sintetik 17α-Methyltestosteron (MT) umumnya digunakan sebagai aditif pakan untuk menghasilkan populasi ikan nila jantan (Oreochromis niloticus). Penggunaan hormon testosteron sintetis tidak dianjurkan di Indonesia. Penelitian ini dilakukan untuk mengevaluasi pengaruh hormon testosteron alami dalam makanan testis banteng (BTM) pada maskulinisasi ikan nila menggunakan metode divalidasi aceto carmine squash, dari gonad ikan. Desain eksperimental dimanfaatkan dua eksperimen faktor dalam desain benar-benar acak. Fry disimpan dalam 40-L akuarium kaca pada kepadatan 40 fry/akuarium. Fry (7 DPH) menerima BTM selama 7 hari (T1), 14 hari (T2) dan 21 hari (T3) dan dosis 0% (D1), 3% (D2), 6% (D3), dan 9% (D4). Ketika pengobatan hasil ini, menunjukkan signifikan (P ≥ 0,05) hanya terjadi maskulinisasi pada kelompok perlakuan dari BTM dan tidak diperlakukan BTM. Pada kelompok diobati BTM, dosis dan durasi pengobatan tidak signifikan. Persentase ikan jantan 83,3% (9%-7d, 9%-21d, 6%-21d: dosis dan durasi, masing-masing), lebih tinggi dari kelompok semua. Tingkat kelangsungan hidup benih (95-99,5%) tidak dipengaruhi oleh pengobatan BTM (tidak ada P yang signifikan ≥ 0,05). Pertumbuhan ikan secara signifikan dipengaruhi oleh BTM pengobatan dibandingkan dengan tidak diobati BTM. Kinerja pertumbuhan tertinggi fry diperoleh dengan BTM 9%.Kata kunci: maskulinisasi, ikan nila, tepung testis sapi